2020
DOI: 10.3390/atmos11121319
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of COVID-19 Lockdown on Mobility and NO2 Concentration in the Lombardy Region

Abstract: Recent observation and modeling-based studies have shown how air quality has been positively affected by the containment measures enforced due to the COVID-19 outbreak. This work aims to analyze Lombardy’s NO2 atmospheric concentration during the spring lockdown. The region of Lombardy is known for having the largest number of residents in Italy and high levels of pollution. It is also the region where the first European confinement measures were imposed by the Italian government. The modeling suite composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…PM 2.5 comes mainly from the combustion of fossil fuels such as car exhaust fumes, coal combustion, etc. PM 10 , in turn, can come from industrial chimneys, dust from construction sites, and fine particles resulting from the interaction of sulfur oxides and nitrogen oxides in the air [34]. In Poland, the most important source of PMs (in particular PM 10 ) is low emission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PM 2.5 comes mainly from the combustion of fossil fuels such as car exhaust fumes, coal combustion, etc. PM 10 , in turn, can come from industrial chimneys, dust from construction sites, and fine particles resulting from the interaction of sulfur oxides and nitrogen oxides in the air [34]. In Poland, the most important source of PMs (in particular PM 10 ) is low emission.…”
Section: Discussionmentioning
confidence: 99%
“…On 30 January 2020, the World Health Organization announced that the new coronavirus epidemic poses a public health threat, and the disease itself has been dubbed corona virus disease 2019 (COVID-19 for short) [31]. To stop the pandemic, unprecedented restrictions were introduced, resulting in a slowdown in the economy, which in turn eliminated or reduced some sources of pollution, including vehicle traffic, construction sites, and coal-fired factories [32][33][34]. However, this did not stop the pandemic, which spread throughout the world over the next few months, affecting most of the world's population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the impact of the lockdown on Lombardy's air quality (Cameletti, 2020;Collivignarelli et al, 2020;Piccoli et al, 2020;Putaud et al, 2020). However, not all results are fully concordant: in fact, while Putaud et al claim that they have not observed any significant changes in PM10 concentrations in Milan, Collivignarelli et al argue that the lockdown had a positive effect on them, as well as on PM2.5 and other air pollutants.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Numerous studies around the world, as in China and East Asia [13][14][15], India [16][17][18], Southeast Asia [19,20], Europe [21][22][23][24][25][26], North America [27,28] and South America [29,30], have analyzed the effect of COVID-19 lockdowns in spring 2020 on concentrations of particulate matter (PM) and gaseous pollutants (NO x , CO, O 3 , SO 2 , NH 3 , etc.). All these studies agree on an unprecedented reduction of air pollution worldwide due to drastic limitations in traffic and industrial activity [31][32][33].…”
Section: Introductionmentioning
confidence: 99%